Correlation between Severity of Dyspepsia and Helicobacter pylori Infection - Gontar Alamsyah Siregar; Sahat Halim (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Dyspepsia is a common complaint in clinical practice. Correlation between Helicobacterpylori (H. pylori) and functional dyspepsia had been reported in many studies, but studies that analyzed theseverity of dyspepsia and H. pylori were limited and the results were controversial. This study is about to knowthe correlation between the severity of dyspepsia and H. pylori infection. Method: A retrospective descriptive analysis to patients with dyspepsia at Permata Bunda Hospital, Medan was done in 2010-2014. Simple random sampling was done to get 44 patients with dyspepsia, 22 are H. pylori positive and 22 patients are H. pylori negative. The severity of dyspepsia assessed with Porto Alegre DyspepticSymptoms Questionnaire (PADYQ) scoring instrument. Univariate and bivariate analysis (Chi-square andSpearman correlation) were done using SPSS version 22. Results: Epigastric pain is the most common symptom in dyspepsia patients. There is a correlation betweenulcer type dyspepsia and H. pylori infection (p = 0.030), while dysmotility type and mixed type were not correlated.The severity of epigastric pain has significant positive correlation with H. pylori (r = 0.386; p = 0.01), while theseverity of other symptoms such as nausea, vomit, and abdominal bloating have negative correlation with H.pylori. Dyspepsia total scoring is significantly lower in H. pylori positive than in H. pylori negative (p = 0.033). Conclusion: There is a positive correlation between the severity of epigastric pain and H. pylori infection,negative correlation between the severity of nausea, vomit, and abdominal bloating and H. pylori infection, andcorrelation between lower dyspepsia total scoring and H. pylori infection.Keywords: dyspepsia, Helicobacter pylori, PADYQ, epigastric pain